ANALISIS PENGEMBANGAN OBYEK WISATA PANTAI OESAPA DI KOTA KUPANG - Febi Adriani Balu; Ronald P C Fanggidae; Paulina Yuritha Amtiran (Journal of Management Small and Medium Enterprises (SMEs), 2019)
This study aims to analyze the supporting and inhibiting factors for the development of Oesapa Beach attractions in Kupang City. This type of research is qualitative research using qualitative descriptive research methods. Data sources consist of primary data obtained through observation and interviews; and secondary data sources come from records, interview results and documents from relevant agencies in the study. The results of the study show that the factors that support the development of Oesapa Beach attractions are: (1) Tourist attraction, is anything that has a unique, easy, and value in the form of natural diversity, culture, and man-made results that are targeted or tourist visits; (2) Visitors, are someone who visits a tourist area with the aim of having fun and spending less time, energy and money in less than 24 hours. While the inhibiting factors for the development of Oesapa Beach attractions are: (1) Accessibility, is the degree of ease achieved by a person towards an object, service or environment; (2) Promotion is an effort to offer products or services with the aim of attracting consumers to buy or consume them; (3) Human Resources (HR), namely the workforce involved in tourism is still inadequate and professional; and (4) Funds, is one of the benchmarks for the progress of the development of sustainable tourism objects. Oesapa Beach has a tourist attraction in the form of beautiful and natural scenery, lopo-lopo lined on the beach, and lined with cafes with colorful tents and unique and different cafe designs. In addition to the tourist attraction, visitors who are increasingly busy visiting this tourist attraction become a supporting factor for tourism objects can be developed. Keywords: Analysis, Obstacle Factors, Supporting Factors, Tourism